STRATEGI MEMBANGUN PERSONAL BRANDING DALAM MENINGKATKAN PERFORMANCE DIRI - DHARMA SETIAWAN (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Marketing a products needs an effective marketing strategy, with the aim that in addition to being able to meet the needs and wants of target consumers, also get positioning as well as reaching a broad market-share. Personally, everyone needs to "marketing yourself" to get a positive positioning and at the same time become top of mind in the minds of others. The process of "marketing yourself" activities can begin by building and promoting personal branding as a major part of the communication tools and processes with the target market and the general public, where their success is indicated by an optimal mind-share and heart-share; meaning the more extensive and in-depth attainment of mind-share and heart-share by a personal branding, the stronger personal branding will be, the higher the value of the person's existence and role in the mind of others, which in turn improves his performance. For example, just by mentioning a person's name, then someone else will immediately be able to imagine and explain who and how the person is. This research is a documentation study about the essence of personal branding which is analyzed by using descriptive-qualitative method.